1979
DOI: 10.1073/pnas.76.7.3233
|View full text |Cite
|
Sign up to set email alerts
|

Contacts between Escherichia coli RNA polymerase and thymines in the lac UV5 promoter.

Abstract: I have identified those 5 positions of thymines in the lac UV5 promoter that lie close to bound Escherichia coli RNA polymerase (nucleosidetriphosphate:RNA nucleotidyltransferase, EC 2.7.7.6). Although ultraviolet irradiation of DNA with 5-bromouracil substituted in place of thymine normally cleaves the DNA at the bromouracils, a protein bound to the DNA can perturb these cleavages at those locations at which the protein lies close to the bromine. In the lac promoter most of these contacts lie in three regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, contact with thymine methyls is not actually demonstrated. Hydrogen bonding sites in an A-T basepair at the site could supply the contact point(s) and indirectly quench the cleavage reaction by other means (12).…”
Section: Thymine Methyls In Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contact with thymine methyls is not actually demonstrated. Hydrogen bonding sites in an A-T basepair at the site could supply the contact point(s) and indirectly quench the cleavage reaction by other means (12).…”
Section: Thymine Methyls In Operatorsmentioning
confidence: 99%
“…Photochemical cleavage of the lac UV5 promoter substituted with shown that at least 10 thymine methyls are covered by RNA polymerase (12,19). Three occur in the -35 site including the two invariant thymines, four occur in the -10 site Including one of the invariant thymines, and three occur in the transcription start site region which is also A-T rich.…”
Section: Thymine Methyls In Operatorsmentioning
confidence: 99%
“…The operon fusion strain was derived from the deletion strain and is called pop5228 [gehotype: HfrC A(gal-attX-bio) rpoBS00 AmalB107 lacL8UVSp lacZ':: mal'K lamB::lac'Z]. In this fusion strain, gene lamB is expressed from the lacL8UV5p promoter (19,23), which is independent of the cap cyclic AMP control. pop5228 was constructed in two steps.…”
Section: E Coli K-12 Pop5217 [Genotype: Hfrc A(gal-attk-bio)mentioning
confidence: 99%
“…RNA polymerase II isolated from wheat germ consists of two very large subunits and a pattern of smaller subunits (Jendrisak & Burgess, 1977) which is typical of eucaryotic RNA polymerase II [see Chambon (1975)]. E. coli RNA polymerase also includes among its subunits two very large species, fi and (S', which have been shown to be that part of the core enzyme which may be chemically cross-linked to DNA (Hillel & Wu, 1978; Simpson, 1979). Perhaps the common occurrence of these very large subunits is responsible for the similar binding domains of the procaryotic and eucaryotic binary complexes.…”
Section: Discussionmentioning
confidence: 99%